Regulasi Pariwisata dan Respon Masyarakat Bali: Analisis Doxey Irritation Index - Ni Wayan Amanda Putri Wijaya (YASIN, 2026)
The rapid growth of tourism in Bali over the past decade has generated increasingly significant physical, social, and ecological pressures, as reflected in the surge of international tourist arrivals reaching 6.3 million in 2024 with a projected 6.5 million in 2025. This phenomenon aligns with the concept of overtourism, whereby tourist numbers exceed the destination’s carrying capacity, as evidenced by waste generation of approximately 3,436 tons per day and a vehicle population of 5.2 million units that surpasses the capacity of regional infrastructure. This study aimed to analyze community responses to these dynamics and to evaluate the effectiveness of government regulations by applying the Doxey Irritation Index framework to communities in Bali. A descriptive qualitative method was employed using literature-based analysis and in-depth interviews. The findings show that at the euphoria stage, the community continues to welcome tourists positively due to the creation of numerous local employment opportunities and increased economic activity. At the apathy stage, the community begins to perceive environmental pressures and recognizes weaknesses in regulations addressing these pressures. Entering the annoyance stage, the intensity of tourist flows becomes more burdensome, and people start to lose private space as a consequence of policies that redistribute tourists to specific areas. At the antagonism stage, tourists are perceived as the primary source of environmental problems, while the government is viewed as having lost legitimacy in tourism governance. These findings indicate that weak policy integration, limited enforcement, and uncontrolled tourism growth are driving Bali’s shift from euphoria toward antagonism, thereby underscoring the need to reformulate tourism policies that are more responsive to social dynamics and regional carrying capacity in order to safeguard the sustainability of tourism in Bali.